Process optimization and characterization of green banana (Musa acuminata x balbisiana cv. Saba) peel flour - Domingo, Kathryn Jan Yadao (College of Home Economics, University of the Philippines Diliman, 2017)
Saba peels were used to produce flour. Face-centered central composite response surface methodology was used to optimize the processing method in terms of yield and lightness. Linear predictive models for response parameters showed that only sodium metabisulfite concentration (p<0.0001) affects lightness while only drying temperature (p=0.0460) influences yield. Models were verified using a generated optimal processing condition (46oC drying temperature and 0.88 %( w/v) sodium metabisulfite) producing 97.95 g/kg flour with 54.16 ± 0.16 lightness. Characterization showed that optimum Saba Peel Flour (SPF) has good solubility (solubility = 9.23 ± 0.26%) and poor swelling power (swelling power = 5.96± 0.18) at 60oC and at room temperature, holds more water than oil (WHC = 2.40 ± 0.06 g/g; OHC = 0.67± 0.02 g/g). It is slightly acidic (pH = 5.56 ± 0.02), has coarse particles (D50 = 0.118 mm), and has relatively low bulk density (bulk density of 0.61 ± 0.19 g/ml). Hence, SPF can be used in viscous products that require heating (i.e. gravies and soups) and are naturally brown (i.e. cookies and brownies). Its coarse particles and poor ability to swell make SPF unsuitable for bakery products that require expansion and smooth consistency. Low OHC limits its application in emulsification systems (i.e. meat products). Lastly, with a low yield, SPF production using the optimized method may be uneconomical. Use of other drying methods is recommended to increase yield and possibly reduce drying time. Studying its carbohydrate composition, other functional properties, and consumer acceptability when used as a flour substitute may reveal more information about the applicability of SPF.